Komplexitätsadaption integrierter Gesamtfahrzeugsimulationen - Netter, Florian (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2016)
Following the research principle of economy the simplest and most suitable simulation model should be preferred over more complex ones. This allows a high goodness of fit to existing measuring data with a high generalizability during the simulation of virtual prototypes. In addition, testing effort and simulation time can be reduced. For this reason quantification attributes are researched in this book, granting an optimal simulation model complexity depending on different simulation purposes.